MODEL PEMBELAJARAN WORD SQUARE BERBANTUAN MEDIA WORD SEARCH PUZZLE DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMP NEGERI 1 BATHIN SOLAPAN - Hesty Widyaningsih; Supentri; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by problems in the learning process at SMP Negeri 1 Bathin Solapan, especially in grade VII, namely low student motivation. This is caused by several factors, including the fact that the learning model is not yet fully implemented. As a result, student involvement in the learning process is still very minimal, and students still tend to have difficulty understanding the learning material. When the material is presented, some students do not take notes, lack enthusiasm in participating in learning activities, quickly give up when encountering difficult questions, and do not focus on the teacher and consider the material explained to be unimportant, because the material is often delivered using conventional methods This can reduce students' motivation to learn. Therefore, the researcher is interested in conducting research to determine the effect of the word square learning model assisted by word search puzzles on improving student motivation in learning Pancasila Education in grade VII at SMP Negeri 1 Bathin Solapan. One of the research questions in this study is whether there is an effect of the word square learning model. The population in this study consisted of 159 students, with a sample size of 63 students divided into two classes, namely class VII.1 and VII.2. The data collection method used in this study was observation (questionnaire). Data management was conducted using statistical analysis with the t-test formula, namely the Independent Sample T-test, yielding a sig. (2-tailed) = 0.000 at a significance level of 5% or 0.000 < 0.05, then Ha is accepted and H0 is rejected.